CRITICAL LISTENING SKILLS WITH AUDIO VISUAL MEDIA INDONESIAN LANGUAGE EDUCATION STUDENTS MUHAMMAD YAMIN SOLOK UNIVERSITY - Mega Putri (Jurnal Ilmu Pendidikan Ahlussunnah, 2022)
Listening is a skill that must be possessed by students. In communicating activities both on campus and in the social environment, students must be able to understand the information seen and heard properly. Understanding in communication is needed so that there are no mistakes in capturing information or ideas that are heard. With a good understanding, the listener can give an opinion on the reading material. This study used descriptive qualitative method. The sample is all students of Indonesian Language Education class of 2019 as many as 12 people. The results of the study were the average value of critical listening skills using audio-visual media for Indonesian Language Education students at Mahaputra Muhammad Yamin Solok University was 78.47 with the following details: 1 person scored 100, 1 person scored 91.67, and 83.33 as many as 5 people, a score of 75 as many as 2 people, a score of 66.67 as many as 1 person and a score of 58.33 as many as 2 people. Audio visual media helps lecturers in providing variations in the learning process so that the learning process is liked by students. With the presence of audio-visual media, the skills of Indonesian students at Mahaputra University Muhammad Yamin Solok with sufficient classification are 78.47.